2014
DOI: 10.1016/j.ijscr.2014.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Case report of rare chronic myelogenous leukemia related multibacterial splenic abscess presenting with scrotal swelling

Abstract: HighlightsSplenic abscesses associated with chronic myelogenous leukemia (CML) are rare. When they occur they are mostly fungal and associated with the immunosuppressive effects of the chemotherapy.Splenomegaly and scrotal swelling can have multiple etiologies and although rare, they can be presenting symptoms of CML.Epididymitis can cause scrotal swelling which may be exacerbated by the effects of splenomegaly upon the systemic circulation promoting venous congestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Deveer et al (7) reported a case of splenic abscess caused by brucellosis in a 21-year-old man, which antibiotic therapy without surgical intervention, was successful. A case reported by McPhillips et al (8) stated that a splenectomy was required due to splenomegaly and scrotal inflammation, subordinate to a multibacterial splenic abscess. Parande et al (9) reported a case regarding a child with splenic abscess triggered from Brucella melitensis biotype 1 with an acute infection was effectively treated with solitary antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Deveer et al (7) reported a case of splenic abscess caused by brucellosis in a 21-year-old man, which antibiotic therapy without surgical intervention, was successful. A case reported by McPhillips et al (8) stated that a splenectomy was required due to splenomegaly and scrotal inflammation, subordinate to a multibacterial splenic abscess. Parande et al (9) reported a case regarding a child with splenic abscess triggered from Brucella melitensis biotype 1 with an acute infection was effectively treated with solitary antibiotics.…”
Section: Introductionmentioning
confidence: 99%